Studi Tingkat Pengetahuan dan Persepsi tentang Kesehatan dan Keselamatan Kerja (K3) Berbasis Gender pada Pekerja Ojek Online di Kota Kupang - Antonius A. Kewohon; Jacob M. Ratu; Soleman Landi (Universitas Nusa Cendana, 2020)
Knowledge and perception about occupational health and safety in a company are essential to prevent work accidents as they can affect behavior at work. The number of accidents in Kupang city involving motorbikes was 276 cases (in 2018). This study aims to determinate differences in knowledge and perceptions of occupational health and safety between male and female online taxibike. This types research is analitic survey by design cross sectional. This study had a sample of 112 taxibike workes, consisting of 61 men and 61 women. The sampling method was accidental sampling. Data were analyzed using t-test (independent sample t-test). The results showed a significant difference between male and female online taxibike regarding perceptions of occupational health and safety while there was no difference between male and female online taxibike regarding knowledge of occupational health and safety. It is necessary for online taxibike companies to conduct health promotion program to increase knowledge and perceptions about occupational health and safety among their workers.